2016
DOI: 10.1111/btp.12326
|View full text |Cite
|
Sign up to set email alerts
|

Tree Height Reduction After Selective Logging in a Tropical Forest

Abstract: By harvesting scattered large trees, selective logging increases light availability and thereby stimulates growth and crown expansion at early‐life stage among remnant trees. We assessed the effects of logging on total and merchantable bole (i.e., lowest branch at crown base) heights on 952 tropical canopy trees in French Guiana. We observed reductions in both total (mean, −2.3 m) and bole (mean, −2.0 m) heights more than a decade after selective logging. Depending on local logging intensity, height reductions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 38 publications
0
31
2
Order By: Relevance
“…Despite previous work linking forest disturbance to variation in D : H relationships (Rutishauser et al. , Kearsley et al. ), we found that, across Gabon as a whole, forest disturbance history (primary, logged, or secondary) only weakly influenced the selection of D : H model.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Despite previous work linking forest disturbance to variation in D : H relationships (Rutishauser et al. , Kearsley et al. ), we found that, across Gabon as a whole, forest disturbance history (primary, logged, or secondary) only weakly influenced the selection of D : H model.…”
Section: Discussioncontrasting
confidence: 99%
“…, Rutishauser et al. ). For these reasons, generic models cannot accurately represent the heterogeneity of an entire georegion or nation of interest, making the landscape‐scale implications of site‐to‐site variation, disturbance history, and habitat types on allometric relationships impossible to determine.…”
Section: Introductionmentioning
confidence: 99%
“…Attention should be taken to high harvest intensities and/or substantial incidental damage due to poor harvesting practices that diminish stocks of survivors, even if they promote recruitment. Most trees that recruit are fast-growing pioneers that are favored by disturbance but are vulnerable to water stress (Bonal et al, 2016) and competition (Valladares and Niinemets, 2008), and because their height is lower than in mature forests (Rutishauser et al, 2016), they might have reduced carbon sequestration potential. With ongoing climate change and increased frequencies and intensities of droughts in Amazonia (Malhi et al, 2008), betting on recruits to store C in forests disturbed by selective logging might thus be a risky gamble.…”
Section: Discussionmentioning
confidence: 99%
“…Our biomass estimates based on the Chave et al. () allometry for our logged forests are potentially positively biased as the database of direct‐harvest trees are primarily from undisturbed forests with only five secondary forest sites, and may not capture the reduction in tree heights observed in logged forests (Rutishauser, Hérault, Petronelli, & Sist, ). The wood density parameter ( p ) captures differences in species composition (Baker et al., ).…”
Section: Methodsmentioning
confidence: 99%